Mitral stenosis in a teenager after rheumatic mitral valve regurgitation valve repair: A case report - Ngardig Ngaba, Neguemadji; Chibuzo, Uzoego Nwakaku; Patel, Meet; Gulati, Amit; Ola, Olatunde; Djindimadje, Allarangué; Khan, Imteyaz A. (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Mitral stenosis (MS) is a widely-known complication of mitral valve repair for non-rheumatic mitral regurgitation (MR). Few reports are available on the occurrence of MS after mitral valve repair for rheumatic MR in young populations. Case summary : A 14-year-old girl presented with orthopnea, abdominal distension, and bilateral lower-limb edema. She was cachectic, with a high-pitched holosystolic murmur best heard at the cardiac apex, bilateral basal crackles, tender hepatomegaly, pitting pedal edema, and jugular venous distension. Antistreptolysin O (ASO) titer was elevated. Transthoracic echocardiography (TTE) revealed loss of central coaptation of the mitral valve with leaflet restriction and MR, annular dilatation of the tricuspid valve and tricuspid regurgitation (TR). She had AHA/ACC stage D mitral and tricuspid regurgitations. Tricuspid annuloplasty and mitral valve repair for rheumatic mitral regurgitation were performed using Carpentier Edward numbers 30 and 34, respectively. Following surgery, the weight and body mass index (BMI) rapidly normalized. The patient also developed progressive MS. Discussion: Previous studies in adults have described the etiopathogenesis of MS after non-rheumatic mitral valve repair. There is a paucity of reports describing the development of MS over the span of months after rheumatic MR valve repair in early pubescent children. Conclusion: Growth spurts during puberty can potentially affect MR repair, as the mitral valve prosthesis based on preoperative BSA (Body Surface Area) is outgrown. There is a need for research on planning, prognostication, and development of an optimal, individualized, and adaptable approach to MR intervention in early pubescence.